MODERN UKRAINIAN HOLOCAUST HISTORIOGRAPHY (Південний архів (історичні науки), 2022)
The purpose of the study is to analyze a range of scientific and source research and describe the stages, directions and approaches to the study of the Holocaust in national historiography. The modern scientific field on the issue includes a significant number of diverse achievements. The authors of the study did not aim to cover its full potential and focused their attention on those works that represent, in our opinion, a certain deepening into the thematic plane. In the process of elaborating historiographical developments, attention was paid to the works that form the all-Ukrainian source-scientific field with an emphasis on studies of the regional specifics of the Holocaust in the South of Ukraine. Methods: the work was performed in the context of problem-thematic historiography, methods of analysis and synthesis were used, which allowed to carry out a certain systematization of historical and scientific developments. The comparative-historical method helped to identify patterns and specific regional features of the topic. General scientific methods, analytical, statistical, logical and others are also comprehensively applied. Results. An objective study of Holocaust events by Ukrainian scholars is based on the determination of their consequences and lessons of universal significance. The essence of the Nazi genocide against the Jewish population as one of the most shameful phenomena in the history of civilization is clearly crystallized in modern scientific work. Full knowledge of the real events of the Holocaust and awareness of their tragic consequences should serve as a warning and incentive to prevent the revival of such phenomena in the future. Conclusions. In domestic historiography, the analysis of the occupiers’ repressive policies aimed at the extermination of the Jewish population during World War II allows us to form a multi-vector view of the recent history of Ukraine and identify the tragic events of the Holocaust by regional realities. The historical and scientific field created in Ukraine about the research has considerable potential for further research in the future.
Keywords: historical source, classification, methodological approaches, scientific developments, monographs, dissertations, regional history.